2021
DOI: 10.1002/aenm.202003766
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Slurries Using Cosolvents and Li Salt Targeting Practical All‐Solid‐State Batteries Employing Sulfide Solid Electrolytes

Abstract: classes of materials, including sulfides (e.g., Li 5.5 PS 4.5 Cl 1.5 : [14,15] ≈10 mS cm −1 ), oxides (e.g., Li 7 La 3 Zr 2 O 12 : [16] 0.5 mS cm −1 ), closo-borates (e.g., 0 . 7 L i ( C B 9 H 10 ) -0 . 3 L i ( C B 11 H 12 ) : [ 12,17] 6.7 mS cm −1 ), and halides (e.g., Li 3 YCl 6 : [18,19] 0.5 mS cm −1 , Li 2.25 Zr 0.75 Fe 0.25 Cl 6 : [20] 1 mS cm −1 ). Furthermore, consideration of multiple aspects, such as mechanical sinterability, cost, and lightness (e.g., Li 6 PS 5 Cl: [14] 1.86 g cm −3 , Li 7 La 3 Zr 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 72 publications
1
34
0
Order By: Relevance
“…To eliminate the ionic transport block effect caused by binders, Jung et al conducted a series of works on favorable ionic contacts in the composite cathode. [389][390][391]396 They first found that the solvate ionic liquid (SIL) Li(G3)TFSI (G3: triethylene glycol dimethyl ether, LiTFSI: lithium bis [trifluoromethanesulfonyl]imide) is chemically stable against sulfides. The addition of trace amounts of Li(G3)TFSI provides an alternative ionic pathway across the commonly poor solid-solid contacts in the composite cathode.…”
Section: Fabrication Of Sheet-type Cathodementioning
confidence: 99%
See 3 more Smart Citations
“…To eliminate the ionic transport block effect caused by binders, Jung et al conducted a series of works on favorable ionic contacts in the composite cathode. [389][390][391]396 They first found that the solvate ionic liquid (SIL) Li(G3)TFSI (G3: triethylene glycol dimethyl ether, LiTFSI: lithium bis [trifluoromethanesulfonyl]imide) is chemically stable against sulfides. The addition of trace amounts of Li(G3)TFSI provides an alternative ionic pathway across the commonly poor solid-solid contacts in the composite cathode.…”
Section: Fabrication Of Sheet-type Cathodementioning
confidence: 99%
“…A co-solvent consisting of less-polar dibromomethane and more-polar hexyl butyrate was employed to dissolve NBR and LiTFSI synergistically, which provides an alternative method to control the dispersion of binders (Figure 16D). 390 In addition, the ester solvents incorporating bulky alkyl groups, such as benzyl acetate, were discovered to dissolve both binders and Li salts while attenuating nucleophilic attacks on sulfides, which enable similar dry ionic conductive polymer binders to be used in the wet slurry process for sheet-type cathodes and SEs (Figure 16E). 391 Tuning the polarity of binders is another strategy to overcome the polarity mismatch among binders, solvents, and sulfides.…”
Section: Fabrication Of Sheet-type Cathodementioning
confidence: 99%
See 2 more Smart Citations
“…137 Very recently, a blend of the less polar dibromomethane solvent and the more polar hexyl butyrate solvents was shown to work synergistically to dissolve NBR and LiTFSI, while preserving the argyrodite-type ISE, forming a SSB with the Li + -conducting NBR-LiTFSI binder. 141 In addition to solvents, the functionality of the polymer also inuences the properties of the ISE-binder composite. Riphaus et al compared the results of several binders poly(styrene-cobutadiene) (SBR), polyisobutene (PIB), polymethyl methacrylate (PMMA), HNBR, polyethylene vinyl acetate (PEVA) with Li 10 -SnP 2 S 12 (LSPS) ISE.…”
Section: Binder-solvent-ise Compatibility In Ise-binder Compositementioning
confidence: 99%